Vogt‐Koyanagi‐Harada disease‐like uveitis induced by nivolumab in metastatic renal cell carcinoma - Hitomi Imai; Tomoyuki Koguchi; Yuki Harigane; Kei Yaginuma; Satoru Meguro; Seiji Hoshi; Junya Hata; Hidenori Akaihata; Soichiro Ogawa; Yoshiyuki Kojima (IJU Case Reports)
Introduction Nivolumab can cause various immune‐related adverse events; it rarely induces Vogt‐Koyanagi‐Harada‐disease‐like uveitis. Vogt‐Koyanagi‐Harada‐disease is reported to be closely associated with human leukocyte antigen‐DR4. Case presentation A 68‐year‐old man with metastatic renal cancer underwent nephrectomy. Computed tomography showed multiple lung tumors, raising suspicion of lung metastases. However, one lung hilar mass was suspected to be primary lung cancer, leading to a lobectomy, which subsequently revealed lung metastases of renal cancer. The patient underwent nivolumab treatment but developed Vogt‐Koyanagi‐Harada‐disease‐like uveitis as an immune‐related adverse event. Human leukocyte antigen‐DR4 alleles were identified, and the uveitis improved with topical steroids. He maintained partial response of lung metastases after nivolumab resumption. Immunohistochemical staining revealed significantly higher human leukocyte antigen‐DR4 expression in lung metastasis than primary renal cancer. Conclusion Despite inducing Vogt‐Koyanagi‐Harada‐disease‐like uveitis, nivolumab controlled cancer progression effectively. Immunohistochemical staining results suggest the potential involvement of human leukocyte antigen‐DR4 expression in both the onset of Vogt‐Koyanagi‐Harada‐disease‐like uveitis and nivolumab efficacy.